PENGEMBANGAN JAGUNG HIBRIDA UNTUK PENINGKATAN PENDAPATAN PETANI DI PASAMAN BARAT - Jastra, Yulmar (Publikasi Penelitian Terapan dan Kebijakan, 2012)
Corn (Zea mays L.) is the second national food crop after rice and its role is increasing in line increase of population, livestock, and industrial development of raw material processed corn. This research is descriptive and qualitative and quantitative done in stages, namely: 1) pre-study within the framework of information gathering neighbors and farmers general conditions in the district of West Pasaman, 2) intensive desk study of the data area and the development of corn hybrids and all information obtained from pre-study activities, 3) observation, the field survey. The purpose of this study are (a) to determine the breadth and potential of hybrid maize development in order to increase farmers' income, (b) to study the cultivation of maize technologies in the development of hybrid maize, and (c) to find out the analysis of hybrid maize farming. The corn planting acreage West Pasaman that use hybrid seeds is estimated 82.7% of the total corn crop district and 17.3% using a variety of derivative or composite lokal. West Pasaman land that could potentially be developed for corn planting area covering 90,200 ha. To make do with increased production of IP- 400 program (4 times a year planting) with a hybrid vareitas 100 days old. Corn hybrids can deliver a profit of Rp 6.126 million, -/ha. When the planting of corn 4 months then the corn farmer's incomeper month of Rp 1,531,500, -.